Study on the seismic response of new staggered story isolated structure under different parameters - Shu, Tong; Li, Hong; Wang, Taize; Liu, Dewen; Yao, Shunzhong; Lei, Min (Frontiers in Earth Science, 2023)
The new staggered story isolated structure is developed according to the base-isolated structure and the mid-story isolated structure. Quantitative calculation and evaluation of seismic damage are very important for structural safety. In this paper, the seismic damage evaluation of a new staggered story isolated is studied by numerical simulation and damage index calculation. A new staggered story isolated structure is established, and the effects of different layers and different chassis areas on the seismic response of the structure are studied. When the position of the bottom isolated layer keeps the same, the upper isolated layer is set at different layers, which is set at the top of the 3rd, 6th and 9th layers. When the upper isolated layer keeps at the top of the 3rd layer, the chassis area is set at a different area, which is 26m×26m, 36m×36m and 46m×46m. The results show that the new staggered story isolated structure has good isolated effects under the ground motion. For the structure with lower upper isolated layer, the inter-layer shear force, inter-layer acceleration and inter-layer displacement are reduced, and the energy dissipation effect of the structure becomes better, the core tube is less damaged and the plastic hinge is less . With the increase of chassis area, the isolated effect of the part above the upper isolated layer is good, while the shear force and acceleration of the part below the upper isolated layer of the structure increase, the damage at the core tube changed little and the appearance of plastic hinge increased. Under earthquakes, with the change of the position of the upper isolated layer and the area of the chassis of the new staggered story isolated structure, the displacement, tensile stress and compressive stress of the isolated bearing still meet the requirements of the standard.